Comparison of the efficacy of ultrasound-guided dextrose 25% hypertonic prolotherapy and intra-articular normal saline injection on pain, functional limitation, and range of motion in patients with knee osteoarthritis; a randomized controlled trial - Alireza Teymouri; Nafiseh Birang; Maryamsadat Fakheri; Aref Nasiri (BMC Musculoskeletal Disorders)
Abstract Background and aims Knee osteoarthritis (OA) is a debilitating condition that manifests as knee pain and dysfunction. Clinicians prefer non-surgical options such as intra-articular injections for mild to moderate disease. Dextrose prolotherapy (DPTx) has been shown to have a beneficial effect on knee OA in the long-term. In this randomized controlled trial (RCT), we aimed to compare DPTx with intra-articular normal saline injection (IA-NS) to treat knee OA in terms of effectiveness and patient-reported outcomes. Methods The study was a double-blind RCT with an allocation ratio of 1:1. We used block randomization to assign patients to each treatment arm. Patients with a visual analog scale of at least 4 for pain, and a Kellgren–Lawrence scale of grade 2 or 3 (mild or moderate disease) were selected and assessed according to eligibility criteria. The participants received either 5 ml of 50% dextrose water or 5 ml of 0.9% sodium chloride. The patients were followed up at 2, 4, and 8 weeks. SPSS software was used for statistical analyses. All results were reported with a confidence interval of 95%, and a p-value of less than 0.05 was considered significant. Results Overall, 55 patients were included in the study, but 50 completed the study process (25 patients in each treatment arm). The mean age of patients with knee OA was 62.98 ± 5.37, ranging from 55 to 74 years. We observed significant improvement in both groups in terms of knee pain, function, and knee extension degree at all follow-up visits (p < 0.001). Although DPTx was associated with better results than IA-NS, the difference was not statistically significant (p > 0.05). The adverse events were limited to injection-site pain and ecchymosis, which resolved by week 4. Conclusion Although we achieved slightly better results with DPTx, this treatment technique was not clinically or statistically superior to IA-NS in terms of knee pain and function in the short-term. Therefore, both DPTx and IA-NS are effective and well tolerated treatment options for knee OA. However, more RCTs are needed to confirm these claims.